2008
DOI: 10.1016/j.immuni.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptor Protein MITA Links Virus-Sensing Receptors to IRF3 Transcription Factor Activation

Abstract: Viral infection triggers activation of transcription factors such as NF-kappaB and IRF3, which collaborate to induce type I interferons (IFNs) and elicit innate antiviral response. Here, we identified MITA as a critical mediator of virus-triggered type I IFN signaling by expression cloning. Overexpression of MITA activated IRF3, whereas knockdown of MITA inhibited virus-triggered activation of IRF3, expression of type I IFNs, and cellular antiviral response. MITA was found to localize to the outer membrane of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
1,248
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 1,275 publications
(1,288 citation statements)
references
References 48 publications
38
1,248
1
1
Order By: Relevance
“…Luciferase reporter plasmids for NF-kB, ISRE and the IFN-b promoters, as well as mammalian expression plasmids for HA-or Flag-tagged RIG-I, RIG-I-N, MDA5, MDA5-N, MDA5-C, VISA, TBK1, MITA and IRF3, were previously described. 7,11,36,37 Expression plasmids for human HA-, Flag-or GFP-tagged HBx and RFP-tagged RIG-I, MDA5 and VISA were constructed by standard molecular biology techniques.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luciferase reporter plasmids for NF-kB, ISRE and the IFN-b promoters, as well as mammalian expression plasmids for HA-or Flag-tagged RIG-I, RIG-I-N, MDA5, MDA5-N, MDA5-C, VISA, TBK1, MITA and IRF3, were previously described. 7,11,36,37 Expression plasmids for human HA-, Flag-or GFP-tagged HBx and RFP-tagged RIG-I, MDA5 and VISA were constructed by standard molecular biology techniques.…”
Section: Methodsmentioning
confidence: 99%
“…VISA is constitutively associated with another mitochondrion-associated adapter protein, MITA/STING, which is also essential for virus-triggered signaling. [11][12][13] VISA is associated with TRAF2 and TRAF6 through its TRAF interaction motifs. 7 TRAF2 and TRAF6 facilitate K63-linked polyubiquitination of receptorinteracting protein and NF-kB essential modulator, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The localization of STING by this group was predominantly shown to be in the endoplasmic reticulum. Almost simultaneously with the study on STING, came another independent report by Zhong et al that identified the same protein as Mediator of IRF3 Activation (MITA), which caused activation of IRF-E in 293 cells (Zhong et al, 2008). Cell fractionation and immunoblot analysis revealed that STING localizes to the outer membrane of mitochondrion.…”
Section: Initial Characterization and Localization Of Stingmentioning
confidence: 90%
“…The c di-GMP binding pocket is constrained such that there is no space for accommodating additional phosphate groups of ATP or GTP. In addition to c di-GMP, STING plays an essential role in TLR independent innate immune responses to sighting of DNA and RNA in the cytoplasm (Zhong et al, 2008;Ishikawa et al, 2009;Nakhaei et al, 2010;Prantner et al, 2010;Barber, 2011b;Ishikawa and Barber, 2011). Loss of STING function has been shown to increase susceptibility of cells to microbial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Such interaction recruits a cytosolic protein kinase TBK1 (TANK-binding kinase 1) that activates transcription factors IRF3/7 (IFN regulatory factor 3/7) to initiate the expression of IFN-b (Baum and Garcia-Sastre, 2010). Recently, MITA (mediator of IRF3 activation) has been characterized as a novel adapter protein to mediate signaling transduction between MAVS and downstream protein kinase TBK1 (Zhong et al, 2008) and also to link cytosolic DNA sensing signal to evoke the expression of IFN-b through activation of TBK1 and IRF3 (Ishikawa and Barber, 2008). The produced IFNs in turn induce the expression of hundreds of ISGs to establish host antiviral state by Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway (Sadler and Williams, 2008;Stark, 2007).…”
Section: Introductionmentioning
confidence: 99%